Eyes on the future – evidence for trade‐offs between growth, storage and defense in Norway spruce. Issue 1 (5th November 2018) - Huang, Jianbei; Hammerbacher, Almuth; Weinhold, Alexander; Reichelt, Michael; Gleixner, Gerd; Behrendt, Thomas; van Dam, Nicole M.; Sala, Anna; Gershenzon, Jonathan; Trumbore, Susan; Hartmann, Henrik
Summary: Carbon (C) allocation plays a central role in tree responses to environmental changes. Yet, fundamental questions remain about how trees allocate C to different sinks, for example, growth vs storage and defense. In order to elucidate allocation priorities, we manipulated the whole‐tree C balance by modifying atmospheric CO2 concentrations [CO2 ] to create two distinct gradients of declining C availability, and compared how C was allocated among fluxes (respiration and volatile monoterpenes) and biomass C pools (total biomass, nonstructural carbohydrates (NSC) and secondary metabolites (SM)) in well‐watered Norway spruce ( Picea abies ) saplings. Continuous isotope labelling was used to trace the fate of newly‐assimilated C. Reducing [CO2 ] to 120 ppm caused an aboveground C compensation point (i.e. net C balance was zero) and resulted in decreases in growth and respiration. By contrast, soluble sugars and SM remained relatively constant in aboveground young organs and were partially maintained with a constant allocation of newly‐assimilated C, even at expense of root death from C exhaustion. We conclude that spruce trees have a conservative allocation strategy under source limitation: growth and respiration can be downregulated to maintain 'operational' concentrations of NSC while investing newly‐assimilated C into future survival by producing SM. Abstract : See also the Commentary on this article byGessler & Grossiord, 222 : 5–7.